Therapeutic use of anti-sclerostin antibody in the treatment of multiple myeloma: A systematic review - Liza Ngomdir; V V Bharathwaj; P Nimmy; R Sindhu; Dinesh Dhamodhar; S Sathiyapriya; D Prabu; M RajMohan (Wolters Kluwer Medknow Publications, 2023)
Multiple myeloma is a malignant cancerous condition that is characterized by abnormal plasma cell production and can lead to bone destruction due to increased osteoclastic activity and decreased osteoblastic activity. Many therapeutic therapies are used to treat diseases, such as chemotherapy and radiotherapy. In recent years, anti-sclerostin antibody treatment has been under investigation for its effect on the multiple myeloma. The present study was conducted to assess the effective therapeutic use of anti-sclerostin antibody in the treatment of multiple myeloma. The literature search was conducted using PubMed, Google Scholar, ScienceDirect, and PubMed Central using the following MeSH terms: "multiple myeloma", "anti-sclerostin antibody", "ubiquitin-proteasome pathway", "proteasome inhibitor", "Wnt pathway". A total of 348 articles were screened. Twenty-five out of 348 were full-text articles assessed for eligibility, and four articles were used in this systematic review. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used for the reporting of this systematic review. A total of four randomized control trials (RCT) were included and used in this systematic review. The anti-sclerostin antibodies were various other drugs, and it was found that the anti-sclerostin antibody was effective in preventing autoantibody formation, decreasing bone destruction, and increasing trabecular bone. Anti-sclerostin antibody was found to be effective in decreasing bone destruction by reducing osteoclastic activity and increasing osteoblastic activity associated with multiple myeloma.